The measurement of the quality of educational spaces through social reporting and social impact assessment - Vincenzo Nunzio Scalcione (Formare)
The need to specify the expected results and to provide activities with frequent feedback appears to be a central element for measuring the educational quality of the places where learning takes place; teaching practices, as social phenomena, entail the need to also extend to users-clients, training stakeholders, the possibility of expressing themselves on the quality of the outcomes produced within learning contexts. The proposed essay therefore highlights the role of social reporting, to measure and evaluate the effectiveness of the organisational-educational performances achieved; at the same time, in order to structure an ever-increasing relationship between education and context, the tool of social impact assessment is highlighted, capable of analyzing the training needs expressed by actors involved in the training intervention project in educational environments.